Does Executives’ Early Pollution Experience Improve the ESG Performance of Enterprises - Lin, Shuyi (Transactions on Economics, Business and Management Research, 2024)
With corporate sustainable development strategy, improving environmental performance can promote corporate prosperity. Early growth experience affects executives’ behavior characteristics and then corporate green development decisions. As for corporate ESG performance, many scholars focus on the relationship between ESG and economic benefits with little research on the strategic driving factors of ESG. Taking Shanghai and Shenzhen A-share listed companies from 2007 to 2022 as samples, this paper analyzes the influence of executives’ early pollution experience on corporate ESG performance. It is found that it greatly improves corporate ESG performance. According to heterogeneity analysis, as for enterprises with greater executives’ power or less local environmental regulation, executives’ pollution experience has a more apparent promotion effect on ESG. Mechanism analysis shows that executives’ early pollution experience promotes corporate ESG performance by enhancing competitive culture and green innovation ability.